2022
DOI: 10.1128/spectrum.02477-22
|View full text |Cite
|
Sign up to set email alerts
|

Two Metalloproteases VdM35-1 and VdASPF2 from Verticillium dahliae Are Required for Fungal Pathogenicity, Stress Adaptation, and Activating Immune Response of Host

Abstract: Verticillium wilt, caused by the notorious fungal pathogen V. dahliae , is one of the main limiting factors for agricultural production. Metalloproteases played an important role in the pathogenic mechanism of pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…This means that all the roots in the figure have a cross-sectional diameter greater than or equal to 1 mm. It should be noted that the healthy root systems had more branching cross-sections than the diseased root systems, which could be ascribed to the fungus also colonizing the ducts and secreting toxins that damage the cells ( Bai et al., 2022 ; Lv et al., 2022 ; Ren et al., 2022 ; Sayari et al., 2022 ). Consequently, cell growth would be hindered, and the number of lateral roots reduces, which provides the possibility of classifying the MRI images of healthy and unhealthy root systems.…”
Section: Resultsmentioning
confidence: 99%
“…This means that all the roots in the figure have a cross-sectional diameter greater than or equal to 1 mm. It should be noted that the healthy root systems had more branching cross-sections than the diseased root systems, which could be ascribed to the fungus also colonizing the ducts and secreting toxins that damage the cells ( Bai et al., 2022 ; Lv et al., 2022 ; Ren et al., 2022 ; Sayari et al., 2022 ). Consequently, cell growth would be hindered, and the number of lateral roots reduces, which provides the possibility of classifying the MRI images of healthy and unhealthy root systems.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that some genes participate in regulating the development of V. dahliae and affect the pathogenicity of V. dahliae in plants (Lv et al, 2022; Zhang et al, 2022). To counter plant cell wall protection, pathogenic fungi should degrade host cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…V. dahliae penetrates its host root and colonizes the plant xylem vessels. In recent years, many genes involved in pathogen penetration, stress response, and carbon source utilization have been characterized, including VdGAL4 (Wen et al, 2023), VdM35‐1 , and VdASPF2 (Lv et al, 2022). In our previous study, we found that GhOPR9 can positively modulate the resistance of cotton to V. dahliae by regulating the JA pathway genes (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To determine abiotic stress, 1 mol/L KCl, 1 mol/L NaCl, 1 mol/L Sorbitol, 0.004% SDS and 0.02% CR were added to PDA medium ( Lv et al, 2022 ; Liu et al, 2023 ). The control group was grown on normal PDA medium.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of micronuclei in necrotic plant tissues can promote the survival of pathogenic bacteria in the soil, creating a significant challenge for disease management in agriculture ( Klimes et al, 2015 ). V. dahliae demonstrates notable variability and co-evolutionary abilities with its host, and its pathogenic mechanism is intricate ( Depotter et al, 2019 ; Lv et al, 2022 ; Zhang et al, 2022 ). The specific interaction between the pathogen and the host remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%